Tail Wags Dog? Time-Varying Information Shares in the Bund Market - Christian Upper; Thomas Werner (Deutsche Bundesbank, 2002)
The flow of information between futures and spot prices may vary over time, in particular during periods of stress. This article analyses the information content of the Bund Future and German government bonds during 1998 and test whether it is constant over time. The use of high-frequency data permits us to capture possible imperfections in the information flows between the two markets. We measure the contributions of trading on the spot and futures markets to price discovery using the information shares approach by Hasbrouck (1995) as well as a recently proposed approach based on the Gonzalo-Granger decomposition. A state-space approach is used to estimate the underlying VECM in the presence of missing values. We test for structural breaks in the pricing relationship between the spot and futures markets and estimate break dates. Although most information is incorporated into prices in the futures market, this does not mean that the spot market is irrelevant for prices discovery. Under normal market conditions, the underlying bonds contribute to 19 to 33 % of the variation in the efficient price. The informational role of the spot market vanishes during episodes of stress. For example, during the two weeks after the recapitalization of LTCM (September 24th to October 8th, 1998), the information share of the spot market dropped to virtually zero and futures prices did not respond to movements in bond prices. All adjustment towards equilibrium took place in the spot market. – – Der Informationsfluss zwischen Kassa- und Terminmärkten kann, insbesondere in Zeiten turbulenter Märkte, zeitlich variieren. Dieser Beitrag analysiert den Informationsgehalt im Bund Future und in den zugrundeliegenden Bundesanleihen für das Jahr 1998 und testet auf zeitliche Konstanz. Unsere Analyse basiert auf Hochfrequenzdaten und erlaubt daher die Untersuchung möglicher Unvollkommenheiten im Informationsfluss zwischen beiden Märkten. Wir messen den Beitrag der Handelstransaktionen auf dem Kassa- und Terminmarkt zum Preisbildungsprozess mit Hilfe des Informationsanteil Ansatzes von Hasbrouck (1995) sowie eines Ansatzes basierend auf der Gonzalo-Granger Zerlegung. Um das zugrundeliegende Fehler-Korrektur-Modell schätzen zu können, wenn Datenlücken vorliegen, wird ein Zustands-Raum-Modell verwendet. Wir testen auf Strukturbrüche im Preisbildungsprozess der Märkte und schätzen die Zeitpunkte der Strukturbrüche. Obwohl die meiste Information in den Preisen der Terminkontrakte enthalten sind, liefert der Kassamarkt einen nicht unerheblichen Beitrag zum Preisbildungsprozess. Unter normalen Marktbedingungen trägt die Bundesanleihe mit 19 bis 33 Prozent zur Bestimmung des Effizienzpreises bei. Der Informationsbeitrag des Kassamarktes verschwindet jedoch während Zeiten mit Marktturbulenzen. Zum Beispiel brach der Informationsanteil des Kassamarktes während der LTCM Rekapitalisierungsphase völlig zusammen. Der Terminkurs reagierte in dieser Phase nicht mehr auf Preisbewegungen am Kassamarkt und die Anpassung an das Arbitragegleichgewicht erfolgte ausschließlich durch den Kassakurs.
Keywords: G14; C32; G12; 330; high-frequency data; market microstructure; future markets; information shares; kalman filter; Börsenkurs; Zinstermingeschäft; Öffentliche Anleihe; Effizienzmarktthese; Informationsverbreitung; Schätzung; Deutschland